Odmiany śmierci i umierania w prozie Ignacego Karpowicza - Kościańczuk, Marcela (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
This article presents mortality as a topic of Ignacy Karpowicz’s texts. Karpowicz multiplies the possible ways of understanding mortality (both at the formal and textual level). The analysis of the theme of mortality in Ignacy Karpowicz’s works is connected with reflection on topics such as routine or repeatability. The author is also interested in the status of reality. The main aim of the article is to analyze the ways in which Ignacy Karpowicz uses different categories which are ambivalent and connected with both mortality and life.